Immunity and Tolerance to Fungi in Hematopoietic Transplantation: Principles and Perspectives - Carvalho, Agostinho; Cunha, Cristina; Bozza, Silvia; Moretti, Silvia; Massi-Benedetti, Cristina; Bistoni, Francesco; Aversa, Franco; Romani, Luigina (Frontiers in Immunology, 2012)
Resistance and tolerance are two complementary host defense mechanisms that increase fitness in response to low-virulence fungi. Resistance is meant to reduce pathogen burden during infection through innate and adaptive immune mechanisms, whereas tolerance mitigates the substantial cost of resistance to host fitness through a multitude of anti-inflammatory mechanisms, including immunological tolerance. In experimental fungal infections, both defense mechanisms are activated through the delicate equilibrium between Th1/Th17 cells, which provide antifungal resistance, and regulatory T cells limiting the consequences of the ensuing inflammatory pathology. Indoleamine 2,3-dioxygenase (IDO), a rate-limiting enzyme in the tryptophan catabolism, plays a key role in induction of tolerance against fungi. Both hematopoietic and non-hematopoietic compartments contribute to the resistance/tolerance balance against Aspergillus fumigatus via the involvement of selected innate receptors converging on IDO. Several genetic polymorphisms in pattern recognition receptors influence resistance and tolerance to fungal infections in human hematopoietic transplantation. Thus, tolerance mechanisms may be exploited for novel diagnostics and therapeutics against fungal infections and diseases.